Attitudes towards highly pathogenic avian influenza (HPAI) and biosecurity mitigation practices in rural Vietnam: a cross-sectional survey - Mairead G Whelan, BHSc; Quynh Ba Le, PhD; David C Hall, PhD (Elsevier, 2019)
Background: An outbreak of highly pathogenic avian influenza (HPAI) between 2004 and 2006 resulted in the culling of 45 million birds, and has jeopardised sustainable agricultural production in southeast Asia. HPAI is highly virulent, and small-scale farms present a high-risk environment for disease transmission between animals and humans. The purpose of this study was to investigate how attitudes towards HPAI influence biosecurity mitigation behaviours such as water source management and sanitation on small-scale farms in Vietnam. Methods: We used a participatory approach that included representation from farmers, government, academia, and industry. We collected cross-sectional data on demographics, farm level production, and attitudes and preferences with respect to HPAI and mitigation strategies in north and south Vietnam (Thai Binh and An Giang Provinces, respectively). A stratified randomised selection of 600 small-scale mixed livestock, crop, and fish farmers were interviewed using questionnaires and in-person interviews. We calculated participant numbers using standard epidemiological sample size formulae with α=0·05. The study was approved by Canadian and Vietnamese ethics boards and participants provided verbal informed consent. Logit regression analysis was used to examine the relation between factors influencing HPAI attitudes and behaviours. Further correlation analysis is under investigation, including Pearson correlation and principal component analysis. Findings: Preliminary results show that half the farmers (51%, n=306) did not treat their water according to UN Food and Agriculture Organization guidelines, and fewer than 7% (n=40) said they would report a suspected HPAI case because of the cost and inconvenience of doing so. However, those farmers who expressed concern about HPAI were more likely to practise mitigation behaviours (p=0·034). Interpretation: These preliminary analyses indicate that biosecurity guidelines may not be consistent with management styles of small-scale farms in Vietnam, but also indicate cause for concern for controlling HPAI on such farms. These results should be of interest to public health and policy authorities addressing HPAI mitigation. Our results may not be generalisable to all small-scale farmers in Vietnam because water sources and farming strategies vary across communes. Funding: Grand Challenges Canada (Grant Number 0231-01 Stars in Global Health Round 4) and IDRC, Ottawa.